Ne bis in idem - Om dubbelbestraffning vid trafikbrott och körkortsåterkallelse - Axelson,Jonas (2014)
Sweden has two different systems of sanctions that may arise when a person has committed a serious offense in traffic. For the same conduct a person can in two different proceedings be sentenced to pay a fee or even imprisonment and also have his driving license withdrawn by the Transport Agency (Transportstyrelsen). In Swedish law the principle of res judicata is to prevent a person from being subject to judicial review or be punished more than once for the same conduct. In Latin the principle is called ne bis in idem and usually referred to as the prohibition of double punishment or double jeopardy. In the European Convention on Human Rights the principle of ne bis in idem is regulated in the Article 4 of Protocol No. 7. This principle should prevent prosecution, trial and punishment to be made more than once for the same offence. The principle is also regulated in Article 50 in The Charter of fundamental rights of the European Union. The question whether the Swedish system with two different proceedings concerning withdrawal of driving license and traffic offense and its compatibility with the convention was in the early 2000’s, more specifically in the case Nilsson v. Sweden, tried in the European Court of Human Rights (ECtHR). The Court then ruled that the Swedish system was compatible with Article 4 of Protocol No. 7. Until June 2013, Sweden had a similar system with two proceedings for punishment for tax offense and tax surcharge. In the case NJA 2013 s. 502 the Supreme Court (Högsta domstolen) condemned the Swedish system. My first question is based on the question whether the new attitude that the Supreme Court (Högsta domstolen) has taken regarding tax offenses and tax surcharge should also apply the system with traffic offenses and withdrawal of drivers license. My second question is wider and based more generally on whether the Swedish order of the license area is compatible with the Convention. With a critical perspective, I have studied mainly legal acts, case law from the ECtHR and Swedish legislative history. The Swedish system with two different proceedings for traffic offenses and the withdrawal of driving license and the question whether its compatible with the European Convention on Human Rights has since the last mentioned rulings been tried in the Swedish lower court. The questions to be answered are whether the withdrawal of a driving license constitutes a criminal sanction and whether a person is considered to be subject to double jeopardy. The ECtHR has ruled that the European Convention is a living instrument that must be interpreted in the light of the present day-conditions. Moreover it has ruled that its provisions must be interpreted and applied in a manner not to become illusory and theoretical but practical and effective. My conclusion is that the system should be assessed similar to the assessment made on the field of taxation. The legal security of individuals should be taken in focus and the European Convention on Human Rights should be interpreted based on present day conditions and change of the Swedish system should be done.
Keywords: processrätt; straffrätt; ne bis in idem; dubbelbestraffning; Europakonventionen; dubbelbestraffningsförbud